Commitment to dendritic cells and monocytes. (16th June 2021) - Ohteki, Toshiaki; Kawamura, Shunsuke; Onai, Nobuyuki
Abstract: Dendritic cells (DCs) and monocytes are widely conserved immune cells in vertebrates that arise from hematopoietic stem cells via intermediate progenitors. The progenitors that strictly give rise to DCs or monocytes have been recently identified both in humans and in mice, thereby revealing their differentiation pathways. Advances in analysis technologies have further deepened our understanding of the development of DCs and monocytes from progenitor population-based to individual progenitor cell-based commitment. Since DC-committed progenitors, common DC progenitors (CDPs) and precursor conventional DCs (pre-cDCs) do not differentiate into monocytes, DCs are a distinct lineage from monocytes, although monocytes can acquire DC functions upon activation at tissues where they arrive.